Kontribusi Artificial Intellegence dalam Membentuk Karakter Siswa MI/SD - Sari, Rita; Sibawaihi, Sibawaihi (Mulya Literasi Publishing, 2024)
The purpose of this research is to discuss the contribution of artificial intelligence to student character at the basic education level. The research method used is qualitative with a literature study. The results of this study reveal that there are three main things about the contribution of AI to the character building of MI/SD students, first, the personalization of learning, second, the impact caused both positively and negatively, and the influence of AI on the character of MI/SD students in learning. Therefore, teachers and parents need to direct students to be smart in using AI as a learning tool, not as the main source of knowledge, because AI is a man-made technology that has limitations in recognizing the psychology of students. AI is utilized to facilitate students' learning and stimulate their thinking.